Facilitated stretching - McAtee, Robert E., 1948- 4 0 16; Charland, Jeff.; 5 (Champaign, IL : Human Kinetics, 2007)
A guide for PNF stretching techniques, including routines for running, golf, swimming, cycling, and other sports.
Understanding the basics of stretching -- Focusing on facilitated stretching -- Using the spiral-diagonal patterns of PNF -- Stretches for the lower extremity -- Stretches for the upper extremity -- Stretches for the neck and torso -- Combining techniques to release fibrotic tissue -- Stretching routines for specific activities -- Routines for common soft tissue injuries.
Includes bibliographical references (p. 177) and index.
Adult;Adult
DVD.
Keywords: 2 -- 0; 6; Stretching exercises;Athletes.;Physical therapy;Stretching exercises.;Athletes.;Physical therapy. -- Popular works.;Popular works; 20; 2